AN ADDITIONAL NOTE ON VIBURNUM CLEMENSAE KERN - KERN, J. H. (REINWARDTIA, 1952)
In "Reinwardtia" (1: 157. 1951) I published a new species of Viburnum from Mount Kinabalu, Borneo, under the name of V. clemensae.The description was drawn up after fruiting specimens in the Herbarium of the Arnold Arboretum. Unfortunately flowers were wanting in the specimens available.Some time ago Dr. A. J. G. H. Kostermans came across much more complete material among the indeterminata of the Bogor Herbarium, profusely flowering as well as fruiting. This enables the amplification of the description.